Domestic violence and international law - Meyersfeld, Bonita (Hart, 2010)
Domestic Violence and International Law argues that certain forms of domestic violence are a violation of international human rights law. The argument is based on the international law principle that, where a state fails to protect a vulnerable group of people from harm, whether perpetrated by the state or private actors, it has breached its obligations to protect against human rights violation. This book provides a comprehensive legal analysis for why a state should be accountable in international law for allowing women to suffer extreme forms of domestic violence and how this can help indivi.